Research of the relief images forming process on the imprints by means of screen UV-varnishes - Piknevych Sergіy; Repeta, Vyacheslav (Journal of Graphic Engineering and Design, 2023)
This article describes the process of relief image forming by UV-varnishes on self-adhesive labels done by means of screen printing plates with different screen mesh - 36 and 90 lines per cm. The influence of substrates’ surface energy on the process of UV-varnish transfer has been investigated. It was defined a disproportional distribution of surface energy on nonprinted self-adhesive paper and it was determined the influence of screen ruling on the varnishing relief’s height as well as the value of substrate’s surface energy and viscosity of UV- varnish.